Mengenal diri sendiri: Langkah awal untuk hidup lebih tenang - Saputra, Micho Triana (Maliki Interdisciplinary Journal, 2025)
Self-awareness is the cornerstone of building inner peace and mental health. This process involves becoming aware of one's emotions, values, strengths, and weaknesses. Many individuals experience anxiety and restlessness because they lack a complete understanding of themselves. This article discusses the concept of self-awareness descriptively, as well as its relationship to academic achievement, body image, and social behavior. Based on three studies conducted by faculty members at UIN Malang, it was found that self-concept significantly influences various aspects of life. This article also discusses practical ways to understand oneself through reflection, mindfulness, and self-evaluation. Understanding and accepting oneself has proven to play a crucial role in building a more peaceful, meaningful, and harmonious life.